Squamous Cell Carcinoma: A Stranger in The Breast - D, Vani; A. N, Sheelashree; N, Apoorva; M, Bharathi (Annals of Pathology and Laboratory Medicine, 2020)
In routine clinical practice, invasive ductal carcinoma of breast is commonly encountered. However strangers do knock the door sometimes and squamous cell carcinoma of breast is one such entity. Although clinical and radiographic features are not specific to this tumour it follows an atypical presentation in terms of tumour size, lymphnode and systemic spread. Usually Squamous cell carcinomas of the breast are triple negative tumours with aggressive behavior and are resistant to standard chemotherapeutic regimens.